Penerapan Teknologi Biodigester Bumdes Arum Mandiri Untuk Pengembangan Integrated Farming Dan Waste To Energy - Erwan Tri Efendi Erwan; Supriyo; Anis Roihatin; Nur Fatowil Aulia (Dharma: Jurnal Pengabdian Masyarakat, 2026)
The limited availability of fossil fuels and their negative impact on the environment has led to the increasing development of alternative energy sources, particularly new and renewable energy. One such alternative energy development is biogas derived from livestock waste. Arum Mandiri, a village-owned enterprise (Bumdes), located in Tegowanu Village, Tegowanu District, Grobogan Regency, manages a cattle farm with eight cows. The manure, which is still managed independently, has so far been used only as organic fertilizer for the community's agricultural needs. One adult cow alone can produce 10-15 kg of manure per day, resulting in nearly 80-120 kg of manure produced daily. However, only 10-20% of the organic fertilizer utilized from the cow manure must first be dried. Unused cow manure is ultimately disposed of, disrupting the environment and producing an unpleasant odor. Therefore, it is necessary to develop appropriate technology to optimize the utilization of cow manure and achieve economic value. The application of biodigester technology to produce biogas is a solution offered, considering its ease of installation and relatively affordable costs, and can promote energy independence. Keywords: cow dung, biogas, digester, renewable energy